Ensuring Compliance and Mitigating Reporting Risks under PP 43/2025: A Governance-Based Perspective on Indonesia’s New Financial Reporting Regime - Rini, Retno Puspa; Rosyadi, Imran (Universitas Widyatama, 2026)
This study examines Indonesia’s Government Regulation No. 43 of 2025 (PP 43/2025), a major reform that restructures national financial reporting obligations by mandating standardized financial statements, digital submission through the Platform Bersama Pelaporan Keuangan (PBPK), competency and integrity requirements for preparers, and formal management responsibility for reporting accuracy. Positioned within governance theory, compliance scholarship, digital financial reporting research, and COSO’s internal control framework, this study employs a qualitative exploratory approach and regulatory mapping to analyse the implications of PP 43/2025 from the perspective of financial statement preparers. The findings demonstrate that PP 43/2025 substantially elevates accountability and transparency through centralized, real‑time, and multi‑agency access to financial statements; however, it simultaneously intensifies compliance pressure and creates new categories of reporting risk—including misstatement risk, governance liability, technological vulnerability, and human‑capital constraints. PBPK’s role as the single authoritative reporting channel increases the visibility and durability of errors, making robust internal controls and governance oversight essential prerequisites for compliance. The study proposes a governance‑based reporting framework that integrates regulatory obligations, COSO‑aligned control mechanisms, and organisational governance structures to mitigate preparer‑side risks. Conceptually, the research advances understanding of how digital regulatory infrastructures reshape financial reporting governance in emerging markets. Practically, it offers preparers, auditors, and regulators a structured foundation for strengthening reporting readiness and internal governance capabilities under the new regulatory regime